Bla ma Rdo rje ʼchaṅ gi rnal ʼbyor sñiṅ gi bdud rtsi bźugs so - Ṅag-dbaṅ-legs-pa, Sga-ston, 1864-1941 (T.G. Dhongthog, 1978)
Instructions on the practice of the guruyoga, a teaching focussing on the contemplative identity of the tutelary deity and the tantric preceptor; according to the Lam ʼbras tradition of the Sa-skya-pa sect.